Does an emergency access button increase the patients’ satisfaction and feeling of safety with the out-of-hours health services? A randomised controlled trial in Denmark - Morten Bondo Christensen; Helle Collatz Christensen; Bo Christensen; L Huibers; Jonas Fynboe Ebert (BMJ Open)
Objective To investigate if the option to bypass the telephone queue can increase satisfaction and feeling of safety in callers.Design Randomised controlled parallel superiority trial. Data from questionnaire survey.Setting Two out-of-hours (OOH) services in Denmark.Participants 217 510 citizens who called the OOH services between 4 September 2017 and 30 November 2017.Randomisation Two-faze study period: First half with randomisation of participants based on their date of birth; even date randomised to intervention, uneven date randomised to control group. Second half with all participants included in intervention group.Intervention Providing randomised callers (intervention group n=146 355) with the option to bypass the telephone waiting line through an emergency access button (EAB), while the rest got the normal service (control group n=71 155). All EAB users were invited to a questionnaire survey as well as random participants who did not use the EAB (of whom approximately 50% did not have the EAB option).Main outcome measures Satisfaction and feeling of safety in callers.Results 2208 of 6704 (32.9%) invited callers answered the questionnaire (intervention group n=1415 (users n=621, non-users n=794); control group n=793). The OR for answering in the two categories with highest satisfaction when provided with the EAB option was 1.34 (95% CI 1.07 to 1.68) for satisfaction with the waiting time, 1.21 (95% CI 0.91 to 1.60) for overall satisfaction and 1.46 (95% CI 1.12 to 1.89) for feeling of safety. Approximately 72% (441/621) of EAB users reported that the EAB option increased their feeling of safety with the OOH services ‘to a high degree’ compared with 25% (197/794) of callers who had the EAB option without using it.Conclusions The EAB can provide fast access to OOH telephone advice in case of severe illness. It favours citizens perceived in most need of urgent healthcare and significantly increases both feeling of safety and patient satisfaction.Trial registration details NCT02572115 (5 October 2015).